Modeling of Art Students' Intellectual Motivating Training in Fundamentals of Philosophy - Ilkevich, Boris V.; Usmanova, Larisa T.; Ilkevich, Konstantin B.; Solovyeva, Nataliya V.; Lisitzina, Tatyana B. (International Review of Management and Marketing, 2016)
Traditional system of students' training in philosophy tends to teach students of all specialties without taking peculiarities of their future vocational activity into account. It does not consider features of art students' training; it is not aimed to develop their intelligence, conceptual and figurative thinking, motivation to study this discipline. In this regard, the article concentrates on the development of a model of art students' intellectual motivating training in fundamentals of philosophy. The leading research method was a modeling method; it presents pedagogical reality in a more updated form that promotes art students' intelligence development and formation of positive motivation to study fundamentals of philosophy. The article provides the essence of the model developed by the authors; its features have been singled out: realization of the principle of students' intellectual motivating training, use of mind maps in the course of students' training, gradual formation of intellectual actions and motivation to study this discipline. The structure of the model proposed by the authors represents the set of interconnected and complementing components: target, content, operational and activity-based, assessing and resultatives. The proposed model of art students' intellectual motivating training in fundamentals of philosophy contributes to the improvement and specification of the existing theory of training philosophy. Materials of the article can be used by teachers of colleges and higher education institutions to select and structure the content of training in philosophy of students mastering different specialties. Keywords: Modeling, Intellectual Motivating Training, Students, Art Specialties. JEL Classifications: A23, I23, I26